Peningkatan Ketahanan Pangan dan Pencegahan Stunting melalui Pemberdayaan Masyarakat dalam Pengembangan Pertanian Terpadu - J, Junios; Yanti, Gusri; Fatdillah, Haezah; Dwi Triani, Hera; Kariman, Delsi; Putri Salsabila, Kharisma; Habibillah, Muhammad (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
PRL Rajo Tigo Selo Farmer Group is a community service partner of Bukittinggi Prima Nusantara University in 2024. The partner is an environmentally friendly farmer group located in Jorong Babukik, Nagari Kamang Mudiak, Agam Regency, with 21 group members. These partners are divided into three divisions: the Agriculture Division, the Livestock Division, and the Agricultural and Livestock Products Processing Division. PRL Rajo Tigo Selo has been involved in agriculture and livestock since the establishment of this farmer group. The problem faced by the partners is the lack of innovation in processing agricultural and livestock products. Well-packaged products are not only attractive to consumers but also meet hygiene and food safety standards. This innovative food processing product is being applied through packaging technology activities to several micro, small, and medium enterprise products belonging to farmer groups, such as galo-galo honey, roasted salted eggs, vegetable nuggets, and green lado duck. The packaging technology using a vacuum sealer and sterilisation tools can extend the shelf life and resistance of products to microbiological damage. Based on this, the community service team conducted training on packaging technologies for farmer group members and UMKM stakeholders in Jorong Babukik to increase the competitiveness of local products. The results of this community empowerment are being used as the main source of stunting prevention in Jorong Babukik, Kamang Mudiak, Agam Regency. The activities carried out include providing counselling on stunting. Agricultural development activities are carried out by using household waste to transform it into compost using biocompost techniques.